2006
DOI: 10.1111/j.1365-2842.2006.01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties and regional differences of human masseter motor units related to three‐dimensional bite force

Abstract: The aim of this study was to estimate numerically the properties of masseter motor units (MUs) in relation to bite force magnitude and direction three-dimensionally and to confirm the hypothesis that the properties differ between different parts of the muscle by means of simultaneous recording of MU activity along with the MU location and three-dimensional (3D) bite force. The MU activity of the right masseter of four healthy men was recorded using a monopolar needle electrode in combination with a surface ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…By this means it was revealed (as far as we are aware, for the first time) that the heterogeneous activation behaviour of the masseter manifests itself even in small muscle subvolumes as a very localised phenomenon at the level of its smallest functional units. These findings confirm the initially stated hypothesis and add substantially to those of previous reports in which task‐specificity was separately proved for individual MUs with locations in distinct muscle regions only. These results are, moreover, also supported by the local muscle activity differences identified at the interference EMG level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By this means it was revealed (as far as we are aware, for the first time) that the heterogeneous activation behaviour of the masseter manifests itself even in small muscle subvolumes as a very localised phenomenon at the level of its smallest functional units. These findings confirm the initially stated hypothesis and add substantially to those of previous reports in which task‐specificity was separately proved for individual MUs with locations in distinct muscle regions only. These results are, moreover, also supported by the local muscle activity differences identified at the interference EMG level.…”
Section: Discussionsupporting
confidence: 91%
“…The regions examined were arbitrarily selected on the basis of geometrical or anatomical considerations. Selective task‐dependent activation of MUs with force‐direction specificity has been detected under such experimental conditions . Simultaneous intra‐muscular recordings obtained from distant parts of the muscle by use of wire electrodes confirmed differential (i.e.…”
Section: Introductionmentioning
confidence: 66%
“…Data from animal studies have suggested that differential activation of the masseter – a phenomenon also described for muscles of other body regions – is reflected mainly by the distinguishable anatomical compartments and the different neuronal supply of the corresponding muscle subdivisions . In this context, selective task‐dependent activation of motor units (MUs) with force‐direction specificity has been detected under different static biting conditions . In a recent study , task‐dependent recruitment of MUs was examined for relatively small subvolumes of the masseter.…”
Section: Introductionmentioning
confidence: 99%
“…Spikes required for STA of force are typically recorded using fine-wire EMG, and the resulting STA has been used to estimate the mechanical action of individual motor units (ter Haar Romeny et al 1984; Thomas et al 1986). It has also been used to study changes in motor unit mechanical properties in a wide variety of contexts, such as during static and dynamic contractions (Keen and Fuglevand 2004;Ogawa et al 2006), whether muscle is activated volitionally or spontaneously firing (Chan et al 2001). Despite some limitations that have been well characterized (Calancie and Bawa 1986;Taylor et al 2002), STA has provided important insights into human motor systems (Gossen et al 2003).…”
Section: Introductionmentioning
confidence: 99%